Unusual molecular mechanisms in the origin of alpha-thalassemia - Ferrão, José (2017)
Hemoglobin (Hb) is a protein responsible for oxygen transportation from lungs to the entire body. It is composed by four globular subunits - the globins - each with a central core containing a heme molecule. Globins are encoded by the α- and β-globin gene clusters located at 16p13.3 and 11p15.5, respectively. The pattern of globin gene expression during development is precisely controlled by the interaction of cis-regulatory genomic regions (located in close proximity to and far from genes) with trans-activating/silencing factors within permissive chromatin domains. Distally upstream of the α-globin genes there are four multispecies conserved sequences (MCS-R1 to R4) which are critical for the expression of the downstream globin genes. Deletions removing the α-globin genes and/or their distal MCSs give rise to α-thalassemia, one of the most common genetic recessive disorders worldwide, due to a reduced rate of α-globin chain synthesis. The severity of the pathology is variable ranging from a very mild microcytic hypochromic anemia to a moderately severe anemia associated with the formation of β4 tetramers resulting in HbH disease or an even higher reduction or complete absence of α-chains resulting in hemoglobin Bart’s hydrops fetalis, a condition generally incompatible with life. The main objectives of this work were to characterize the molecular lesions underlying ten Portuguese cases of unusual α-thalassemia/HbH disease and to understand their origin and functional consequences. After exclusion the most frequent molecular lesions associated with α-thalassemia, Multiplex Ligation-dependent Probe Amplification (MLPA) using the SALSA MLPA P140B HBA kit (MCR-Holland) was used to search for DNA deletions in the subtelomeric region of chromosome 16p. Additionally, specifically designed synthetic MLPA probes, as well as gap-PCR and Sanger sequencing were performed for more accurate deletion breakpoint mapping. We have found five distinct deletions and one indel, all in heterozygosity. The deletions range from approximately 3.3 to 323 kb and two of them are novel. The three larger deletions remove the entire α-globin cluster whereas the others remove totally or partially the distal regulatory elements keeping the α-globin genes structurally intact. The indel comprises the deletion of the MCS-R2 regulatory element and the insertion of a singular 39 bp DNA fragment possibly originating from a complex rearrangement involving chromosome 3. Finally, no α-globin gene cluster deletion or point mutation were found in a patient who revealed to be a very unusual case of acquired alpha-thalassemia associated with a myelodysplastic syndrome. Our study widens the spectrum of molecular lesions and unusual molecular mechanisms by which α-thalassemia/HbH may occur and emphasizes the importance of diagnosing large α0-deletions to provide patients with appropriate genetic counseling.